Nontraditional Approach for Interprofessional Service Learning in a Doctor of Physical Therapy Program: The Farm Worker Family Health Program - Garcia, Jodan D.; Frank, Rachael Anne (Frontiers in Communication, 2016)
Interdisciplinary service learning opportunities are recognized as valuable educational tools for healthcare students, including those in physical therapy doctoral programs. However, it is unclear what components of these service learning initiatives are most successful for preparing students to collaborate as part of a healthcare team and communicate with diverse patient populations. The Farm Worker Family Health Program, based on a community academic partnership model, enables healthcare students from several disciplines to treat migrant workers during the annual farmworker migration. This program offers students the opportunity to provide beneficial medical attention to an underserved population, hone clinical practice techniques and critical thinking, and build inter-professional communication skills. The experience may benefit students by not only enriching their skills as novice clinicians, but also by deepening their sense of empathy. The present article describes how this opportunity has been incorporated into a physical therapy graduate program, and explores the implications of melding immersive interdisciplinary civic engagement with physical therapy education in order to foster clinical and communication skills.